Net illumination is more effective for reducing fisheries bycatch at night - Kayla M. Burgher; Kyli E. Denton; John Wang; S. Hoyt Peckham; Daniel Aguilar-Ramirez; Jesse F. Senko (Reviews in Fish Biology and Fisheries, 2026)

Geomorphological dynamics at the coast: A sedimentary stratigraphy for Atlit-Yam, the earliest coastal village at the Eastern Mediterranean and its submerged landscape - Vishal Kataria; Gilad Shtienberg; Isaac Ogloblin Ramirez; Roni Zuckerman-Cooper; Nimer Taha; Elle Grono; Marko Runjajić; Ehud Galili; Nicolas Waldmann; David E. Friesem (Quaternary International, 2026)

A modified-live PRRSV vaccine administered at weaning confers partial protection against a highly virulent PRRSV-1 strain throughout the grower-finisher period - A. Pey; P. Curto; E. Gurri; E. Aulinas; G. Ramirez; J. Molín; L. Fraile; A.M.M. Stoian (Research in Veterinary Science, 2026)

Coastline evolution, submerged landscape, and island occupation: Preliminary insight on Pleistocene-Holocene coastal environments of south-eastern Sicily - Isaac Ogloblin Ramirez; Ehud Galili; Christian A. Tryon; Fabrizio Antonioli; Sara E. Zaia; Peyton Carroll; Elizabeth M. Niespolo; Lauren D. Gilmore; Sebastiano Di Mauro; Fabio Portella; Gianmarco Minniti; Carmelo Monaco; et al. (Quaternary International, 2026)

Evaluation of in vitro digestibility and fermentability of black soldier fly (Hermetia illucens) and housefly (Musca domestica) meal as feed ingredients for growing pigs - Kiyonori Kawasaki; Junliang Zhao; Christian Ramirez-Camba; Toshiya Kawasaki; Isaac J. Salfer; Gerald C. Shurson; Pedro E. Urriola (Animal Feed Science and Technology, 2026)

Weaving Indigenous and Western knowledge systems across a continuum of knowledge and decision-making spaces - Natalie C Ban; Hannah V Watkins; Robyn E Forrest; Alejandro Frid; Carrie A Holt; Sierra J Hall; Christina N Service; Luisa Ramirez; Daniel L Curtis; Kyle L Wilson; Lawrence Ignace; Andrea J Reid; et al. (Current Opinion in Environmental Sustainability, 2026)

Place attachment and agroforestry adoption - Alexandra R. Ramirez; Sarah E. Castle; Chloe B. Wardropper (Agroforestry Systems, 2026)
Conventional row crop farming in the United States is associated with multiple environmental challenges including soil and water degradation and decreased biodiversity. Sustainable agriculture advocates have encouraged agroforestry, or the integration of woody perennial crops like trees and shrubs into agricultural systems, to ameliorate environmental challenges and provide on-farm benefits. Despite promised environmental benefits and efforts to increase adoption, rates of agroforestry practice remain low in the US. Researchers have long studied how agricultural decision-making is shaped by psychological, financial, institutional, and logistical challenges, but there is less attention on the role of emotional and cultural factors in the adoption of new agricultural practices. Through interviews with 31 farmers (both adopters and non-adopters of agroforestry) in Illinois, we examine how place attachment, or the cognitive and emotional bonds between people and place, influences the long-term investment decisions associated with agroforestry. We find that place attachment is expressed through distinct dimensions: place dependence, place identity, and place affect. While specific attachments like connection to nature and family legacy often motivate adoption, attachments related to economic dependence on the land and traditional farming identities are sometimes barriers to adoption. Our findings suggest that outreach and extension work on agroforestry may be improved by explicitly acknowledging place-specific values and emotions.

Possible Evidence for Sea Salt Production by Solar Evaporation at a Newly Discovered Submerged Neolithic Site off the Carmel Coast, Israel - Ehud Galili; Vered Eshed; David E. Friesem; Isaac Ogloblin-Ramirez (Journal of Marine Science and Engineering, 2026)
The submerged Early Holocene landscape of the Carmel Coast (Israel) has yielded remarkable evidence of Neolithic settlements and their associated material culture, preserved on and within the seafloor. Here, we report on the preliminary documentation of a newly discovered submerged Neolithic site near N. Mearot Inlet, containing series of rectangular clay basins arranged in a grid pattern. Following their initial identification, sediment cores were extracted from the basins and the ramparts around them and analyzed for their pollen, phytoliths, and mineralogical composition; however, more samples are to be taken and the analyses have yet to yield more conclusive results. Comparisons with later case studies suggest that the polygonal cracking of the clay and the basins’ morphology, size, and spatial organization are more consistent with salt evaporation pans, which were operated ca. 7000 years BP, than with plot-and-berm agricultural use, though agricultural use cannot be ruled out entirely.

Petrography and pore-scale assessment of CO2 mineral trapping potential of sedimentary strata beneath the lower mainland British Columbia, Canada - Paula Ramirez-Lopez; Shahin E. Dashtgard; Marc Enter; Matthew Power; Dirk Kirste; Maziyar Nazemi; Francyne Bochi do Amarante (International Journal of Greenhouse Gas Control, 2026)

Securing the future of Colombian cacao: projected suitability changes and adaptation strategies under climate change - Tobias Fremout; Carlos E. González-Orozco; Viviana Ceccarelli; Erika K. Ramirez-Siniva; Evert Thomas (Regional Environmental Change, 2026)

Continental‐wide prioritization of protected areas to address global and habitat‐specific goals for avian biodiversity conservation - Yanjie Xu; Diego Pavón‐Jordán; Tyler Hallman; Tristan R. M. Bakx; Lluís Brotons; Sergi Herrando; Alison Johnston; Brett K. Sandercock; Thomas Sattler; Alaaeldin Soultan; Vitalie Ajder; Dawn E. Balmer; et al. (Conservation Biology, 2026)
The United Nations and European Union have set ambitious conservation goals to halt and reverse declines in biodiversity by protecting 30% of land and sea areas by 2030. Effective conservation planning requires evidence‐based spatial prioritization to maximize the coverage of species within designated protected areas. Based on a pan‐European database for occurrence and abundance of breeding birds collected in the 2010s, we applied the Zonation algorithm to identify key areas that would maximize the protection of ranges and populations for 435 species of breeding birds across Europe using either continental or national prioritization targets. When 30% of Europe's highest priority terrestrial areas were selected by the algorithm, 49% of species’ ranges and 63% of species’ populations were protected. When 10% and 30% of the highest priority lands were selected, compared with prioritization using occurrence data, prioritization using abundance data resulted in a higher percentage of species’ populations, especially rare and range‐restricted species, being represented for protected area coverage. Stratifying prioritization by habitat criteria greatly enhanced habitat‐specific conservation efficiency, enabling coverage of over 80% of breeding bird species’ populations in tundra, Mediterranean, and coastal habitats with a selection of 10% of the highest priority areas for each. Our prioritization supports international targets adopted under the Kunming–Montreal Global Biodiversity Framework by identifying key areas and providing a roadmap to guide optimal site protection and conservation planning in Europe.

Intentional take of seabirds for human consumption: a global review to inform conservation and policy needs for migratory species - Jonathan M. Handley; Joanne Morten; G. Barry Baker; Aline Küehl-Stenzel; Maximin K. Djondo; Graeme A. Taylor; Iván Ramirez; Heidrun Frisch-Nwakanma; Noëlle F. Kümpel; Tammy E. Davies (Biological Conservation, 2026)

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Identifying factors influencing Hydroxytyrosol in wines: Varietal selection, organic management, and yeast strategies in rosé and white wine production - M. Gonzalez-Ramirez; A.B. Cerezo; A.M. Troncoso; B. Puertas; E. Cantos-Villar; M.C. Garcia-Parrilla (Food Chemistry, 2026)

Physicochemical Characterization of Potato Peel Flour (Solanum tuberosum L.) and Optimization of the Ultrasound-Assisted Extraction Process (UAE) of the Phenolic Compounds Using Response Surface Methodology - Rayssa Dias Batista; Eduardo Ramirez Asquieri; Aline Gomes de Moura e Silva; Ryhára Dias Batista; Danilo José Machado de Abreu (Potato Research, 2026)
The objective of this research was to characterize potato peel flour, evaluate which solvent was best for extracting the phenolic compounds (PC), and optimize the ultrasound-assisted extraction by investigating the linear and squared effects and their interaction in recovering these compounds using an RCCD experimental design and response surface methodology associated with a desirability graph. The potato peel was donated by a local restaurant in the city of Goiânia (GO), and the results obtained for the physicochemical composition confirmed to those expected for this residue. Six solvents were used to extract the PC (ether, ethanol, water, methanol-acetone-water, 60% ethanol in water, and 10% ethanol in water), and the results showed that 10% ethanol in water gave the best results for total PC and antioxidant activity. A second RCCD experimental design was then used to obtain the ideal parameters for the ultrasound, and it was observed that, to obtain a fitted model that predicted the ideal extraction conditions with confidence, one must use three variables in the design: time, temperature, and the solid-liquid ratio. According to the response surface and desirability graphs, the ideal conditions to maximize the extraction of phenolic compounds from potato peels were: a time of 66.9 min, a temperature of 44.9 °C, and a solid-solvent ratio of 1:46.82 m/v. Thus, both the ultrasound and the experimental design helped maximize the recovery of PC from the potato peel flour.

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Land Use Change Reshapes Climate‐Driven Diversity Patterns of Tropical Arbuscular Mycorrhizal Fungi - Justin D. Stewart; Dario X. Ramirez; Antonio Leon‐Reyes; Noelia Barriga; Sol Llerena; Bethan F. Manley; Natalia Carpintero‐Salvador; Melany Ruiz‐Uriguen; Jos M. Raaijmakers; E. Toby Kiers; James T. Weedon (Molecular Ecology, 2026)
Land use change and agricultural expansion threaten biodiversity yet the effects on soil life remain poorly understood, especially for microbes. Arbuscular mycorrhizal (AM) fungi are microbes that form associations with most plant species and are essential for plant nutrient uptake. The diversity of these fungi is also sensitive to both land use change and regional climatic conditions. We therefore asked whether variation in AM fungal diversity is driven by land use change, and whether these effects are further influenced by interactions with temperature and precipitation gradients. To test this, we quantified AM fungal biodiversity in cultivated and adjacent uncultivated soils across a 1700 m elevational gradient (temperature: 7.7°C–16.5°C and precipitation: 1000–3500 mm). We found that conversion of uncultivated soils to agriculture reduced AM fungal richness by 80%, on average. Richness in uncultivated soils increased with the temperature gradient, while richness in farms declined. A similar but inverted trend was found for precipitation, where richness in uncultivated sites declined as precipitation increased. Uncultivated soils contained approximately three‐fold more unique AM fungal species compared to cultivated soils. Our findings demonstrate that interactions between climate and land use strongly influence AM fungal biodiversity patterns in tropical mountain ecosystems. Incorporating both factors into conservation and sustainable agriculture strategies will be critical to preserving belowground biodiversity under global change.

Relocated, range-limited, but resilient: niche shift and constraints on spread in introduced Nanday parakeets (Aratinga nenday) - Brenda R. Ramirez; Diego C. Blanco; John E. McCormack (Urban Ecosystems, 2025)
Introduced species often encounter novel environments that test their capacity for ecological flexibility and adaptation. We investigated ecological niche dynamics in Nanday Parakeets ( Aratinga nenday ), a naturalized parrot species in Los Angeles, to assess whether their introduced range reflects a shift from their native range in South America. Using principal components analysis and niche overlap tests, we found that the introduced population occupies a distinct environmental space—cooler, drier, and with less tree cover—with no measurable niche overlap. Habitat suitability modeling in Los Angeles suggests that their current habitat is narrowly concentrated in south-facing coastal canyons and not in more arid inland or high-elevation areas. Data from iNaturalist show that Nanday Parakeets roost and feed mainly in sycamore trees. The 2025 Palisades Fire impacted only 3% of suitable habitat, while the 2018 Woolsey Fire impacted 12%, neither with an observable effect on the population. Our results highlight the contradiction apparent in many species introductions: niche flexibility during establishment combined with ecological constraints on later spread.

Connecting the dots: integrating citizen science, ecology, and habitat change for the conservation of three Leporidae species in the central mountains of Mexico - Eric O Ramírez-Bravo; Evangelina E. Camargo-Rivera; C. Sánchez-Lewy Aldana; F. Amador-Cruz; M. A. Mora-Ramirez (The Science of Nature, 2025)
Anthropogenic activities have a profound impact on ecosystems, threatening species and contributing to increased extinction rates. Among them are some Leporidae species, for which ecological data remains insufficient to support effective conservation. This study aimed to monitor the status of the volcano rabbit ( Romerolagus diazi ), eastern cottontail ( Sylvilagus floridanus ), and Mexican cottontail ( Sylvilagus cunicularius ) in 2018 in southern Mexico City, using citizen science tools. The field research involved recording fecal pellets and habitat characteristics along 1 km transects. Vegetation changes over the past 20 years were analyzed using the Standardized Precipitation Index (SPI), Enhanced Vegetation Index (EVI), and Standard Anomaly Index (SAI). Among 2,026 quadrants (~ 8,000 km²), the volcano rabbit, eastern cottontail, and Mexican cottontail were detected in 3.25%, 8.09%, and 12.37% of sampling points, respectively. Canonical correspondence analysis revealed that mature tree density harmed the presence of the volcano rabbit. At the same time, cottontails appeared to be more resilient to habitat changes. Despite reforestation efforts, SPI, EVI, and SAI data indicated an increase in dryness over time. Intensive planting has transformed alpine grasslands, a key habitat for the volcano rabbit, into densely forested areas. Citizen science is an effective tool for monitoring certain species of leporids, such as the volcano rabbit, and provides valuable insights for conservation strategies. Future interventions should prioritize the preservation of alpine grasslands to ensure their long-term survival.

Oncology Education in Latin America: A Systematic Review of Curricular Gaps, Teaching Strategies, and Regional Initiatives - Jheremy S. Reyes; Cristian S. Cabezas; Luis M. Navarro-Ramirez; David F. Estupiñan-Pepinosa; Arash S. Jalisi-Guevara; Diego A. Vivas-Giraldo; Jheremy E. Reyes-Castellanos (Journal of Cancer Education, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Chlorpyrifos and Persistent Organic Pollutants (POPs) in body feathers of Magellanic penguin (Spheniscus magellanicus) from wintering areas in coastal Argentina - Florencia E. Fernandez; Juan Pablo Seco Pon; Germán O. García; Rocío Mariano-Jelicich; Cristina Ramirez; Karina S.B. Miglioranza (Marine Pollution Bulletin, 2025)

Inhibiting Amikacin Resistance in Multidrug-Resistant Bacteria with Cadmium and Pyrithione - Angel J. Magaña; David Ngo; Kenneth Burgos; Carolina Dominguez Maldonado; Omniya Abdelmaksoud; Jan Sklenicka; Tung Tran; Fernando Pasteran; Verónica Jimenez; María S. Ramirez; Marcelo E. Tolmasky (Current Microbiology, 2025)
The ongoing antibiotic resistance crisis is one of the most pressing public health challenges. Multidrug-resistant bacterial pathogens are reaching the point where some are becoming untreatable. Consequently, besides discovering novel antibiotics, alternative strategies must be explored to manage the problem. One approach is developing inhibitors that overcome resistance to antibiotics currently in use. Resistance to aminoglycosides such as amikacin is mainly due to aminoglycoside-modifying enzymes. Despite being refractory to most resistance enzymes, the semisynthetic amikacin is inactivated by aminoglycoside 6′- N -acetyltransferases type I [AAC(6′)-I], of which AAC(6′)-Ib is the most common in Gram-negative pathogens. The discovery that certain divalent and monovalent cations interfere with enzymatic acetylation catalyzed by AAC(6′)-Ib opens possibilities for developing formulations combining antibiotics with these cations to enhance efficacy. Addition of CdCl₂ to in vitro enzymatic assays inhibited transfer of an acetyl group to the 6′- N position of amikacin, kanamycin, and tobramycin. Hence, Cd 2 ⁺ is a potential adjuvant to aminoglycosides for treating AAC(6′)-Ib-mediated resistant infections. It was initially disappointing that, as with other divalent cations, CdCl₂ addition to cultures of bacteria harboring AAC(6′)-Ib did not reverse resistance. However, the inhibitory action of Cd 2 ⁺ became evident when combined with the ionophore pyrithione. The complex efficiently inhibited resistance in Acinetobacter baumann ii and Klebsiella pneumoniae harboring AAC(6′)-Ib. Furthermore, the combination inhibited amikacin resistance in carbapenem-resistant K. pneumoniae clinical isolates. These results add another cation to the arsenal of potential aminoglycoside adjuvants, which could be developed alone or in coordination complexes with ionophores to treat multidrug-resistant infections.

Optical and particulate properties of dust aerosols in El Paso, Texas - German Rodriguez Ortiz; Manisha Mehra; Mackenzie Ramirez; Sujan Shrestha; Sascha Usenko; James Flynn; Rebecca J. Sheesley; Thomas E. Gill (Atmospheric Research, 2025)

Subterranean pupation: a refuge for non-target species from a prospective biological control agent of the avian vampire fly in Galapagos - Ismael E. Ramirez; Alyssa T. Gooding; Katherine A. Albán; Saúl J. Aguirre; Paolo Piedrahita; Charlotte E. Causton; George E. Heimpel (BioControl, 2025)
The invasive avian vampire fly, Philornis downsi (Diptera: Muscidae), poses a significant threat to Darwin's Finches and other endemic bird species in the Galapagos Islands, and the importation of specialized natural enemies is a promising strategy for its long-term control. The parasitoid Conura annulifera (Hymenoptera: Chalcididae) has received the most attention as a potential biological control agent thus far, including studies assessing its potential to attack non-target species. The potential native and endemic non-target species that are hypothetically most at risk from a release of C. annulifera are those closely related to P. downsi, which include carrion flies in the families Calliphoridae, Muscidae, and Sarcophagidae. In other parts of the world, many of the species that belong to these families pupate in the soil, and since C. annulifera is an obligate pupal parasitoid, we hypothesized that subterranean pupation would constitute a spatial refuge from parasitism, lessening the risk of non-target effects. We thus investigated the burrowing behavior of carrion flies that are endemic and native to Galapagos using introduced flies as surrogates when we could not locate related endemic or native species. We also evaluated the ability of C. annulifera to locate and attack underground puparia of these species. Our trials revealed that, of nine species of carrion fly species tested, eight exhibited subterranean pupation. This included the Galapagos endemic sarcophagids Sarothromyiops dasycnemis and Galopagomyia inoa . Notably, C. annulifera females did not exhibit burrowing behavior and thus were not able to locate or attack subterranean puparia. Our study suggests a low level of risk to endemic and native non-target fly species in Galapagos since many of these species are known to or are expected to pupate within the soil.

Application of a high-density microelectrode array assay using a 3D human iPSC-derived brain microphysiological system model for in vitro neurotoxicity screening of environmental compounds - Kelly E. Carstens; Elena Gronskaya; David Jäckel; Jessica Bertoli; Kelvin Ramirez Cuevas; Julien Dorier; Shan Wang; David Lopez-Rodriguez; Timothy J. Shafer; Marie-Gabrielle Zurich; David Pamies (Archives of Toxicology, 2025)
Unraveling the associations between human exposure to environmental chemicals and potential neurotoxicity presents significant challenges. Evaluation of neurotoxicity potential using animal testing is resource-intensive (financial, labor, and animal use) and faces uncertainties regarding biological relevance to human health outcomes. Therefore, there is a need to develop efficient and human-relevant in vitro new approach methodologies (NAMs) to screen and evaluate chemicals for neurotoxicity potential. Recording of neural network activity using microelectrode array (MEA) technology has been identified as a reliable and reproducible method for evaluating neurotoxicity. Much of this research has been performed in 2D rodent-derived cell models. The ‘BrainSpheres MEA assay’ described in this study offers a promising functional human induced pluripotent stem cell (iPSC)-derived 3D brain model comprising neurons, astrocytes, and oligodendrocytes. We demonstrate consistent spontaneous neuronal firing and network bursting parameters from 7-week-old BrainSpheres using a high-density MEA technology. The performance of this model as a human-relevant NAM was evaluated by conducting a multi-concentration, 13 day exposure study with a set of ten chemicals. Neural activity metrics were assessed and compared to results from a 2D-MEA assay using rodent cells. Loperamide and domoic acid (two assay positive controls) demonstrated similar bioactivity profiles in the BrainSphere MEA assay to the 2D-MEA assay, while acetaminophen (assay negative control) was inactive in both assays. The 2D-MEA model demonstrated more potent bioactivity for 4/7 chemicals that were active in both assays. In the future, reducing replicate variability and testing a larger set of chemicals will likely improve the accuracy and reliability of the assay. These preliminary findings suggest that the BrainSphere assay could be used alongside the rat network formation assay (rNFA) as part of a tiered strategy, where hits in the rNFA are confirmed and further characterized in the BrainSphere model, helping move toward animal-free toxicological testing.

Subcortical white matter hyperintensities and motor function in parkinson’s disease: findings from the ONDRI study - Daniela Cristina Carvalho de Abreu; Frederico Pieruccini-Faria; Anthony E. Lang; Benjamin Cornish; William McIlroy; Mandar Jog; Mario Masellis; Joel Ramirez; Christopher Scott; Sean Symons; Sandra E. Black; Stephen R. Arnott; et al. (GeroScience, 2025)

Effect of long-term retrogradation on the crystallinity, vibrational and rheological properties of potato, corn, and rice starches - Gonzalo Velazquez; Cristian Felipe Ramirez-Gutierrez; Guadalupe Mendez-Montealvo; Rodrigo Velazquez-Castillo; Luis Fernando Morelos-Medina; Eduardo Morales-Sánchez; Marcela Gaytán-Martínez; Mario E. Rodríguez-García; Brenda Contreras-Jiménez (Food Chemistry, 2025)

Biostimulant Effects of Iodine on the Biomass, Biomolecules, and Nutritional Profile of Lettuce Seedlings - Angie Tatiana Ortega-Ramirez; Oscar Silva-Marrufo; Yazmin E. Perez-Rubio; Oscar G. Alaniz-Villanueva; Jaime Herrera-Gamboa; Rubén I. Marin-Tinoco; Pablo Preciado-Rangel; Oscar Sariñana-Aldaco (Journal of Soil Science and Plant Nutrition, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Modeling green infrastructure as a flood mitigation strategy in an urban coastal area - Martijn Kriebel; Ting Liu; Robin Noordhoek; Leonie Staas; Jose E. Ramirez-Marquez; Valentina Prigiobbe (Urban Ecosystems, 2025)

Transient plasma enhanced combustion of ultra-lean H2 in an internal combustion engine for reduced NOx emission - Boxin Zhang; Mariano Rubio; Joshua E. Tobar Lam; Aimee Ortiz-Ramirez; Travis Riggs; Oscar Hernandez; Yushan Chen; Caleb Medchill; Fokion Egolfopoulos; Stephen B. Cronin (Fuel, 2025)

Optimized CO2 photoreduction using cuprous oxide (Cu2O) nanoparticles synthesized using Psidium guajava extract - S. Torres-Arellano; E. Luevano-Hipolito; Mayte G. Fabela-Cedillo; J. L. Aleman-Ramirez; Leticia M. Torres-Martínez; P. J. Sebastian (Energy, Ecology and Environment, 2025)
This work aims to propose earth-abundant materials for CO 2 photoreduction to generate renewable solar fuels to provide practical solutions to global warming. The selected material in this case is cuprous oxide (Cu 2 O), one of the most promising photocatalysts for CO 2 photoreduction due to its high affinity to solar radiation and electronic properties. Cu 2 O nanoparticles (NPs) were synthesized using Psidium guajava residue for the photocatalytic CO 2 reduction. The aqueous residue of the Psidium guajava fruit proved to be suitable for stabilizing and acting as a reducing agent for the synthesis of Cu 2 O NPs. The XRD analysis confirmed the formation of the cubic structure of Cu 2 O. The nanoparticles absorb light from 430 nm with a direct bandgap value of around 1.8 eV. Cu 2 O NPs exhibited activity for CO 2 photoreduction, whose efficiency was optimized by an orthogonal Taguchi L 9 design. The factors studied were catalyst loading, air flow, and temperature. During the use of Cu 2 O NPs in the CO 2 photoreduction HCOOH was identified as the main product, with an optimized production of 103.4 µmol h − 1 under visible light. Also, it was demonstrated the photocatalytic activity of the Cu 2 O NPs for H 2 evolution by water splitting. Graphical Abstract

In vitro and in vivo investigations on the use of yellow mealworm (Tenebrio molitor) as a novel protein feed ingredient for fattening lambs - L.E. Robles-Jimenez; S. Angeles; A.H. Ramirez-Perez; B. Fuente; V. Velazquez-Ordoñez; E. Cardoso-Gutierrez; M. Renna; L. Rastello; M.T. Capucchio; T. Hassan; L. Gasco; J.M. Pino-Moreno; et al. (Animal Feed Science and Technology, 2025)

Tree Diversity Increases Carbon Stocks and Fluxes Above—But Not Belowground in a Tropical Forest Experiment - Florian Schnabel; Joannès Guillemot; Kathryn E. Barry; Melanie Brunn; Simone Cesarz; Nico Eisenhauer; Tobias Gebauer; Nathaly R. Guerrero‐Ramirez; I. Tanya Handa; Chris Madsen; Lady Mancilla; Jose Monteza; et al. (Global Change Biology, 2025)
International commitments advocate large‐scale forest restoration as a nature‐based solution to climate change mitigation through carbon (C) sequestration. Mounting evidence suggests that mixed compared to monospecific planted forests may sequester more C, exhibit lower susceptibility to climate extremes and offer a broader range of ecosystem services. However, experimental studies comprehensively examining the control of tree diversity on multiple C stocks and fluxes above‐ and belowground are lacking. To address this gap, we leverage data from the Sardinilla experiment in Panama, the oldest tropical tree diversity experiment, which features a gradient of one‐, two‐, three‐ and five‐species mixtures of native tree species. Over 16 years, we measured multiple above‐ and belowground C stocks and fluxes, ranging from tree aboveground C, over leaf litter C production, to soil organic carbon (SOC). We show that tree diversity significantly increased aboveground C stocks and fluxes, with a 57% higher gain in aboveground tree C in five‐species mixtures compared to monocultures (35.7 ± 1.8 vs. 22.8 ± 3.4 Mg C ha −1 ) 16 years after planting. In contrast, we observed a net reduction in SOC (on average −11.2 ± 1.1 Mg C ha −1 across diversity levels) and no significant difference in SOC 3 stocks (the predominantly tree‐derived, i.e., C 3 plant‐derived SOC fraction) between five‐species mixtures and monocultures (13.0 ± 0.9 vs. 15.1 ± 1.3 Mg C ha −1 ). Positive tree diversity effects persisted despite repeated climate extremes and strengthened over time for aboveground tree growth. Structural equation models showed that higher tree growth in mixtures enhanced leaf litter and coarse woody debris C fluxes to the soil, resulting in a tightly linked C cycle aboveground. However, we did not observe significant links between above‐ and belowground C stocks and fluxes. Our study elucidates the mechanisms through which higher tree diversity bolsters the climate mitigation potential of tropical forest restoration. Restoration schemes should prioritize mixed over monospecific planted forests.

Evaluation of Chenopodium quinoa (Willdenow) malting parameters on the quality of a red Ale craft beer supplemented with Pilsen base malt and caramel malt - William E. López-Rodríguez; Jhoselyn L. Ramirez-Gutierrez; Miuller D. Morales Valdiviezo; Janet E. Muñoz-Agreda; Korey S. Paredes-Barrios; Juanita Analí Ponce-Ramirez; Melisa S. Barco-Jara; Maria de Fatima Arevalo-Oliva; Guisela P. Carbajal-Romero; Jorge Domínguez; Gilbert Rodríguez; Elza Aguirre (Journal of Cereal Science, 2025)

Site selection for the second Flyeye telescope: A simulation study for optimizing near-earth object discovery - D. Föhring; L. Conversi; M. Micheli; E. Dölling; P. Ramirez Moreta (Icarus, 2024)

Corticotropin releasing hormone receptor 1 in the medial prefrontal cortex mediates aversion resistant alcohol intake - Miranda E. Arnold; Cecelia E. Harber; Lauren A. Beugelsdyk; Ellie B. Decker Ramirez; Grace B. Phillips; Jesse R. Schank (Psychopharmacology, 2024)

Effect of Nicotine on Pulmonary Pathogenic Bacteria - Adrián Rodríguez-Carlos; Oscar E. Gonzalez-Muniz; Maria G. Ramirez-Ledesma; Bruno Rivas-Santiago (Current Microbiology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

LP-44 Enhanced interpretation of secondary pharmacology data through automated visualization tools to support safety assessment - E. Desfosses; S. Ramirez; F. Tillier; T. Jolas; M. Rigault; A. Otto-Bruc; S. Raynal (Toxicology Letters, 2024)

Estimation of macro and micronutrient concentrations in ‘valencia’ orange leaves at different phenological stages using multispectral image analysis and multiple regression - P. P. Gomes de Oliveira; C. A. Da Silva-Junior; J. H. Barron-Zambrano; E. Neri-Ramirez; A. Diaz-Manriquez; E. Osorio-Hernandez; R. Delgado-Martinez (International Journal of Remote Sensing, 2024)

Sex differences in visuospatial cognition- a female advantage in jigsaw puzzle solving - Daniela E. Aguilar Ramirez; Jarrod Blinch; Kurt Robertson; Joseph Opdenaker; Claudia L. R. Gonzalez (Experimental Brain Research, 2024)

Sediment analysis and water quality assessment in the Pixquiac basin: drinking water supply of Xalapa city (Veracruz, Mexico) - M. C. Dupont; E. Martinez-Tavera; P. F. Rodriguez-Espinosa; A. G. Hernandez-Ramirez; P. Guadarrama Guzmán (Environmental Monitoring and Assessment, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Attenuated incubation of ethanol-induced conditioned taste aversion in a model of dependence - Lindsey A. Ramirez; Kathryn R. Przybysz; Joseph R. Pitock; E. Margaret Starr; Hyerim Yang; Elizabeth J. Glover (Psychopharmacology, 2024)

Bumble bee responses to climate and landscapes: Investigating habitat associations and species assemblages across geographic regions in the United States of America - Morgan E. Christman; Lori R. Spears; Emily K. Burchfield; William D. Pearse; James P. Strange; Ricardo A. Ramirez (Global Change Biology, 2024)
Bumble bees are integral pollinators of native and cultivated plant communities, but species are undergoing significant changes in range and abundance on a global scale. Climate change and land cover alteration are key drivers in pollinator declines; however, limited research has evaluated the cumulative effects of these factors on bumble bee assemblages. This study tests bumble bee assemblage (calculated as richness and abundance) responses to climate and land use by modeling species‐specific habitat requirements, and assemblage‐level responses across geographic regions. We integrated species richness, abundance, and distribution data for 18 bumble bee species with site‐specific bioclimatic, landscape composition, and landscape configuration data to evaluate the effects of multiple environmental stressors on bumble bee assemblages throughout 433 agricultural fields in Florida, Indiana, Kansas, Kentucky, Maryland, South Carolina, Utah, Virginia, and West Virginia from 2018 to 2020. Distinct east versus west groupings emerged when evaluating species‐specific habitat associations, prompting a detailed evaluation of bumble bee assemblages by geographic region. Maximum temperature of warmest month and precipitation of driest month had a positive impact on bumble bee assemblages in the Corn Belt/Appalachian/northeast, southeast, and northern plains regions, but a negative impact on the mountain region. Further, forest land cover surrounding agricultural fields was highlighted as supporting more rich and abundant bumble bee assemblages. Overall, climate and land use combine to drive bumble bee assemblages, but how those processes operate is idiosyncratic and spatially contingent across regions. From these findings, we suggested regionally specific management practices to best support rich and abundant bumble bee assemblages in agroecosystems. Results from this study contribute to a better understanding of climate and landscape factors affecting bumble bees and their habitats throughout the United States.

Safe plates in the school space: Investigating compliance of food safety standards among school-based food service providers - Realyn Q. Salvador; Charizza Mae T. Borromeo; Gary C. Alnas; Shaira Vita Mae G. Adviento; Alma C. Asuncion; Mark R. Limon; Arnelyn B. Esteban; Aprilyn A. Gajete; Shiela Mae L. Garcia; Jherie-Mae R. Parico; Christian Jay P. Pungtilan; Jaypee Carl D. Respicio; et al. (Food and Humanity, 2024)

Comparing environmental impacts of deep‐seabed and land‐based mining: A defensible framework - A. Metaxas; C. D. Anglin; A. Cross; J. Drazen; M. Haeckel; G. Mudd; C. R. Smith; S. Smith; P. P. E. Weaver; L. Sonter; D. J. Amon; P. D. Erskine; et al. (Global Change Biology, 2024)
The crises of climate change and biodiversity loss are interlinked and must be addressed jointly. A proposed solution for reducing reliance on fossil fuels, and thus mitigating climate change, is the transition from conventional combustion‐engine to electric vehicles. This transition currently requires additional mineral resources, such as nickel and cobalt used in car batteries, presently obtained from land‐based mines. Most options to meet this demand are associated with some biodiversity loss. One proposal is to mine the deep seabed, a vast, relatively pristine and mostly unexplored region of our planet. Few comparisons of environmental impacts of solely expanding land‐based mining versus extending mining to the deep seabed for the additional resources exist and for biodiversity only qualitative. Here, we present a framework that facilitates a holistic comparison of relative ecosystem impacts by mining, using empirical data from relevant environmental metrics. This framework (Environmental Impact Wheel) includes a suite of physicochemical and biological components, rather than a few selected metrics, surrogates, or proxies. It is modified from the “recovery wheel” presented in the International Standards for the Practice of Ecological Restoration to address impacts rather than recovery. The wheel includes six attributes (physical condition, community composition, structural diversity, ecosystem function, external exchanges and absence of threats). Each has 3–5 sub attributes, in turn measured with several indicators. The framework includes five steps: (1) identifying geographic scope; (2) identifying relevant spatiotemporal scales; (3) selecting relevant indicators for each sub‐attribute; (4) aggregating changes in indicators to scores; and (5) generating Environmental Impact Wheels for targeted comparisons. To move forward comparisons of land‐based with deep seabed mining, thresholds of the indicators that reflect the range in severity of environmental impacts are needed. Indicators should be based on clearly articulated environmental goals, with objectives and targets that are specific, measurable, achievable, relevant, and time bound.

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Galenic formulations of Cannabis sativa : comparison of the chemical properties of extracts obtained by simple protocols using lipidic vehicles - Matías E. Aguirre; Dalila E. Orallo; Patricia A. Suárez; Cristina L. Ramirez (Natural Product Research, 2024)

Recruitment of Row Crop Farmers into a Research Study to Assess Farm Hazards - Victor A. Soupene; D. Erik Boonstra; Joseph E. Cavanaugh; Fredric Gerr; Marizen Ramirez; Adam F. Moskowitz; Carri Casteel (Journal of Agromedicine, 2024)

Epibionts affect the growth and survival of Argopecten purpuratus (Lamarck, 1819) cultivated in Samanco Bay, Peru - Rómulo E. Loayza-Aguilar; Juan Carhuapoma-Garay; Kelly Ramos-Falla; Guillermo B. Saldaña-Rojas; Yolanda P. Huamancondor-Paz; Luis Campoverde-Vigo; Fernando Merino; Gustavo E. Olivos-Ramirez (Aquaculture, 2024)

Optimization of the Polarized Imaging Nephelometer (PI-Neph) for continuous monitoring of multiwavelength aerosol phase functions in support of space polarimetry missions - E. Bazo; J.V. Martins; D. Perez-Ramirez; A. Valenzuela; G. Titos; A. Cazorla; D. Fuertes; M. Weiss; A. Turpie; C. Li; F.J. García-Izquierdo; I. Foyo-Moreno; et al. (Atmospheric Environment, 2024)

How Good Is Online Information for Patients on the Treatment for Luminal Gastrointestinal Cancers? A Comprehensive Evaluation in English and Spanish - Renato Beas; Cielo Cabanillas-Ramirez; Diego Izquierdo-Veraza; Andres Chapoñan-Lavalle; Dalton Norwood; Karina Sato-Espinoza; Adrian Riva-Moscoso; Isabella Ribaudo; Mirian Ramirez-Rojas; Azizullah Beran; Eleazar E. Montalvan-Sanchez (Journal of Cancer Education, 2023)

Effect of an acute long-duration exercise bout on skeletal muscle lipid droplet morphology, GLUT 4 protein, and perilipin protein expression - Sudip Bajpeyi; Jehu N Apaflo; Victoria Rosas; Keisha Sepulveda-Rivera; Armando Varela-Ramirez; Jeffrey D Covington; Jose E Galgani; Eric Ravussin (European Journal of Applied Physiology, 2023)

A randomized placebo-controlled trial of nicotinamide riboside in older adults with mild cognitive impairment - Miranda E. Orr; Eithan Kotkowski; Paulino Ramirez; Darcy Bair-Kelps; Qianqian Liu; Charles Brenner; Mark S. Schmidt; Peter T. Fox; Anis Larbi; Crystal Tan; Glenn Wong; Jonathan Gelfond; et al. (GeroScience, 2023)

Evaluating Participant Recipe Changes in a Healthy Meal Kit Intervention for Families with Low Income - E. McNulty; K. Chambers; R. Zambrano; I. Ramirez; A. Mitchell; L. House; A. Mathews; K. Shelnutt (Journal of the Academy of Nutrition and Dietetics, 2023)

Identifying pollution dynamics using discrete Fourier transform: From an urban-rural river, Central Mexico - P.F. Rodriguez-Espinosa; Jorge Fonseca-Campos; K.M. Ochoa-Guerrero; A.G. Hernandez-Ramirez; J. Tabla-Hernandez; E. Martínez-Tavera; E. Lopez-Martínez; M.P. Jonathan (Journal of Environmental Management, 2023)

P22-21: A 3D human iPSC-derived brain model coupled to multi-well high-density microelectrode arrays (HD-MEA) to improve in vitro neurotoxicity screening of environmental compounds - D. Pamies; K. Carstens; E. Gronskaya; D. Jaeckel; J. Bertoli; K. Ramirez; T. Shafer; M.-G. Zurich (Toxicology Letters, 2023)

Effect of pelleting on the enzymatic digestibility of corn stover - Xueli Chen; Antonio C. Freitas dos Santos; Diana M. Ramirez Gutierrez; Peiyuan Song; John E. Aston; David N. Thompson; James H. Dooley; Michael R. Ladisch; Nathan S. Mosier (Bioresource Technology, 2023)

Gold recovery improvements in grinding and flash flotation circuit - Ramón Arellano-Piña; Elvia Angélica Sanchez-Ramirez; E. Emmanuel Vázquez-Sánchez; Roberto Pérez-Garibay; Jaime Cristóbal Rojas-Montes (Minerals Engineering, 2023)

Perception of NUEVA (Nutrition for Underserved Elders via Application) Usability During Alpha-Testing - Selena N. Ramirez; Cassandra M. Johnson; Apan Qasem; Alexandra E. Cagle; Lesli Biediger-Friedman (Journal of Nutrition Education and Behavior, 2023)

Revised Paleozoic depositional history of the central Rocky Mountains (Utah and Colorado) - Paul M. Myrow; Michael Hasson; John F. Taylor; Lidya Tarhan; David A. Fike; Gerardo Ramirez; George Fowlkes; Leonid E. Popov; Hangyu Liu; Jitao Chen (Sedimentary Geology, 2023)

Real-time COVID-19 Education to Reduce Workplace Risks: Thematic Analysis of a COVID-19 Agricultural Employer Webinar Series - Caitlin G. Jones; Yajaira Ramirez Sigala; Teresa Andrews; Heather E. Riden (Journal of Agromedicine, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Integrated Multi-Trophic Aquaculture (IMTA): Strategic model for sustainable mariculture in Samanco Bay, Peru - Rómulo E. Loayza-Aguilar; Yolanda P. Huamancondor-Paz; Guillermo B. Saldaña-Rojas; Gustavo E. Olivos-Ramirez (Frontiers in Marine Science, 2023)
The development of industrial mariculture in Peruvian coasts will continue to grow according to global trends; however, it is characterized by being mostly monospecific, resulting in ecosystemic impacts due to organic matter, which deteriorate the benthic system and encourage eutrophication, negatively affecting biodiversity and fishery resources, which in a long term could turn the activity into an unsustainable practice. Therefore, it is imperative to adopt new production models, focused on the sustainability principle, such as Integrated Multi-Trophic Aquaculture (IMTA), that allow for greater efficiency, competitiveness, and profitability, while guaranteeing environmental balance. In this context, the present study has addressed the problem of Argopecten purpuratus cultivation in Samanco Bay, in which, based on a diagnosis of the bay's conditions, details of the cultivation, and a thorough analysis of the IMTA concept, a strategic model for mariculture is proposed in order to be adopted by private companies, after a validation process. These concepts can be transferred for their adaptation to other scenarios. Furthermore, it is expected that the academic sector, private companies, and the competent authority will be able to intervene synergistically in this process.

Lessons learned in knowledge co-production for climate-smart decision-making - Alyssa Rosemartin; Theresa M. Crimmins; Katharine L. Gerst; Erin E. Posthumus; Aaron R. Ramirez; Cynthia SA Wallace; Toni Lyn Morelli (Environmental Science & Policy, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Species, growth form, and biogeographic diversity of summit vegetation along an elevation gradient in the tropical Andes: a baseline for climate change monitoring - Luis D. Llambi; Luis E. Gámez; Roxibell Pelayo; Carmen J. Azócar; Jesús E. Torres; Nelson J. Márquez; Monica B. Berdugo; Francisco Cuesta; Lirey A. Ramirez (Journal of Mountain Science, 2022)

Improving cervical cancer screening rates: a scoping review of resources and interventions - Madyson L. Popalis; Sarah I. Ramirez; Kelsey M. Leach; Marni E. Granzow; Kelsey C. Stoltzfus; Jennifer L. Moss (Cancer Causes & Control, 2022)

A First Record of Organochlorine Pesticides in Barn Owls (Tyto alba) from Portugal: Assessing Trends from Variation in Feather and Liver Concentrations - I. Roque; R. Lourenço; A. Marques; E. Martínez-López; S. Espín; P Gómez-Ramirez; A. J. García-Fernández; A. Roulin; J. E. Rabaça (Bulletin of Environmental Contamination and Toxicology, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Contribution of warm habitat to cold‐water fisheries - Nick Hahlbeck; William R. Tinniswood; Matthew R. Sloat; Jordan D. Ortega; Matthew A. Wyatt; Mark E. Hereford; Ben S. Ramirez; David A. Crook; Kara J. Anlauf‐Dunn; Jonathan B. Armstrong (Conservation Biology, 2022)
A central tenet of landscape ecology is that mobile species depend on complementary habitats, which are insufficient in isolation, but combine to support animals through the full annual cycle. However, incorporating the dynamic needs of mobile species into conservation strategies remains a challenge, particularly in the context of climate adaptation planning. For cold‐water fishes, it is widely assumed that maximum temperatures are limiting and that summer data alone can predict refugia and population persistence. We tested these assumptions in populations of redband rainbow trout ( Oncorhynchus mykiss newberrii ) in an arid basin, where the dominance of hot, hyperproductive water in summer emulates threats of climate change predicted for cold‐water fish in other basins. We used telemetry to reveal seasonal patterns of movement and habitat use. Then, we compared contributions of hot and cool water to growth with empirical indicators of diet and condition (gut contents, weight–length ratios, electric phase angle, and stable isotope signatures) and a bioenergetics model. During summer, trout occurred only in cool tributaries or springs ( 25 °C). During spring and fall, ≥65% of trout migrated to the lake (5–50 km) to forage. Spring and fall growth (mean [SD] 0.58% per day [0.80%] and 0.34 per day [0.55%], respectively) compensated for a net loss of energy in cool summer refuges (–0.56% per day [0.55%]). In winter, ≥90% of trout returned to tributaries (25–150 km) to spawn. Thus, although perennially cool tributaries supported thermal refuge and spawning, foraging opportunities in the seasonally hot lake ultimately fueled these behaviors. Current approaches to climate adaptation would prioritize the tributaries for conservation but would devalue critical foraging habitat because the lake is unsuitable and unoccupied during summer. Our results empirically demonstrate that warm water can fuel cold‐water fisheries and challenge the common practice of identifying refugia based only on summer conditions.

Differential effects of aging on spatial abilities - Daniela E. Aguilar Ramirez; Jarrod Blinch; Kate Takeda; Jennifer L. Copeland; Claudia L. R. Gonzalez (Experimental Brain Research, 2022)

Sources, Characteristics, and Therapeutic Applications of Mesenchymal Cells in Tissue Engineering - Rosa Angelica Gonzalez-Vilchis; Angelica Piedra-Ramirez; Carlos Cesar Patiño-Morales; Concepcion Sanchez-Gomez; Nohra E. Beltran-Vargas (Tissue Engineering and Regenerative Medicine, 2022)

Anti-oxidant and anti-inflammatory effect of polar extracts obtained from waste product of wine making - M. J. Germanó; M. D. Muñoz; M. C. Della-Vedova; G. E. Feresin; M. Rinaldi-Tosi; R. D. Enriz; D. C. Ramirez; F. A. Giannini (Natural Product Research, 2021)

Behavior of the Avian Parasite Philornis downsi (Diptera: Muscidae) in and Near Host Nests in the Galapagos Islands - Courtney L. Pike; Ismael E. Ramirez; David J. Anchundia; Birgit Fessl; George E. Heimpel; Charlotte E. Causton (Journal of Insect Behavior, 2021)
The Avian Vampire Fly, Philornis downsi , has invaded the Galapagos Islands, where it causes high mortality of endemic and native landbird species, including most species of Darwin’s finches. Control methods are under development, but key information is missing about the reproductive biology of P. downsi and the behavior of flies in and near nests of their hosts. We used external and internal nest cameras to record the behavior of P. downsi adults within and outside nests of the Galapagos Flycatcher, Myiarchus magnirostris , throughout all stages of the nesting cycle. These recordings showed that P. downsi visited flycatcher nests throughout the day with higher fly activity during the nestling phase during vespertine hours. The observations also revealed that multiple P. downsi individuals can visit nests concurrently, and that there are some interactions among these flies within the nest. Fly visitation to nests occurred significantly more often while parent birds were away from the nest than in the nest, and this timing appears to be a strategy to avoid predation by parent birds. We report fly mating behavior outside the nest but not in the nest cavity. We discuss the relevance of these findings for the adaptive forces shaping P. downsi life history strategies as well as rearing and control measures.

Effect of Serum Albumin, a Component of Human Pleural Fluid, on Transcriptional and Phenotypic Changes on Acinetobacter baumannii A118 - Casin Le; Camila Pimentel; Marisel R. Tuttobene; Tomas Subils; Krisztina M. Papp-Wallace; Robert A. Bonomo; Luis A. Actis; Marcelo E. Tolmasky; Maria Soledad Ramirez (Current Microbiology, 2021)

Improved Segmentation of the Intracranial and Ventricular Volumes in Populations with Cerebrovascular Lesions and Atrophy Using 3D CNNs - Emmanuel E. Ntiri; Melissa F. Holmes; Parisa M. Forooshani; Joel Ramirez; Fuqiang Gao; Miracle Ozzoude; Sabrina Adamo; Christopher J. M. Scott; Dar Dowlatshahi; Jane M. Lawrence-Dewar; Donna Kwan; Anthony E. Lang; et al. (Neuroinformatics, 2021)

Influence of pregnancy and non-fasting conditions on the plasma metabolome in a rat prenatal toxicity study - S. Ramirez-Hincapie; V. Giri; J. Keller; H. Kamp; V. Haake; E. Richling; B. van Ravenzwaay (Archives of Toxicology, 2021)

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

A Review of Translational Magnetic Resonance Imaging in Human and Rodent Experimental Models of Small Vessel Disease - Michael S. Stringer; Hedok Lee; Mikko T. Huuskonen; Bradley J. MacIntosh; Rosalind Brown; Axel Montagne; Sarah Atwi; Joel Ramirez; Maurits A. Jansen; Ian Marshall; Sandra E. Black; Berislav V. Zlokovic; et al. (Translational Stroke Research, 2021)
Cerebral small vessel disease (SVD) is a major health burden, yet the pathophysiology remains poorly understood with no effective treatment. Since much of SVD develops silently and insidiously, non-invasive neuroimaging such as MRI is fundamental to detecting and understanding SVD in humans. Several relevant SVD rodent models are established for which MRI can monitor in vivo changes over time prior to histological examination. Here, we critically review the MRI methods pertaining to salient rodent models and evaluate synergies with human SVD MRI methods. We found few relevant publications, but argue there is considerable scope for greater use of MRI in rodent models, and opportunities for harmonisation of the rodent-human methods to increase the translational potential of models to understand SVD in humans. We summarise current MR techniques used in SVD research, provide recommendations and examples and highlight practicalities for use of MRI SVD imaging protocols in pre-selected, relevant rodent models.

Conscious and unconscious brain responses to food and cocaine cues - Corinde E. Wiers; Jizheng Zhao; Peter Manza; Kristina Murani; Veronica Ramirez; Amna Zehra; Clara Freeman; Kai Yuan; Gene-Jack Wang; Sükrü Barış Demiral; Anna Rose Childress; Dardo Tomasi; et al. (Brain Imaging and Behavior, 2021)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Petrophysical Correlations for the Permeability of Coquinas (Carbonate Rocks) - M. C. O. Lima; E. M. Pontedeiro; M. Ramirez; A. Boyd; M. Th. van Genuchten; L. Borghi; P. Couto; A. Raoof (Transport in Porous Media, 2020)
The pore structure of many carbonate formations is known to be very complex and heterogeneous. Heterogeneity is manifested by the presence of different types, sizes, and shapes of pores resulting from sedimentation and diagenetic actions. These complexities greatly increase uncertainties in estimated rock hydraulic properties in that different permeability values may occur for samples having similar porosities. In order to understand the effects of pore structure and heterogeneity, petrophysical analyses were performed on coquina samples from the Morro do Chaves Formation (Barremian, Sergipe-Alagoas Basin), which is an analogue of Brazilian Pre-salt oil reservoirs of Itapema Formation in the Santos Basin. Routine core analyses, and NMR and MICP measurements were carried out to obtain pore body and pore throat distributions. Obtained T 2 relaxation times were converted to pore size radii by matching the NMR and MICP curves. Pore-scale imaging and pore network modelling were performed using microCT scans and the PoreFlow software, respectively. Calculated permeabilities using PoreFlow showed excellent agreement with the routine laboratory measurements. Samples having pore bodies with a higher coordination number showed much larger permeabilities at similar porosities. This study includes a statistical analysis of various features that caused the observed differences in permeability of the coquinas, including the role of connectivity of the entire porous system. Limitations and challenges of the various techniques, and the imaging and pore-scale flow simulations, are discussed.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

An evaluation of visuospatial skills using hands-on tasks - Daniela E. Aguilar Ramirez; Jarrod Blinch; Claudia L. R. Gonzalez (Experimental Brain Research, 2020)

Contrasting reproductive biology of two hydrothermal gastropods from the Mid-Atlantic Ridge: implications for resilience of vent communities - J. Marticorena; M. Matabos; J. Sarrazin; E. Ramirez-Llodra (Marine Biology, 2020)

Future distribution of early life stages of small pelagic fishes in the northwestern Mediterranean - F. Maynou; A. Sabatés; E. Ramirez-Romero; I. A. Catalán; V. Raya (Climatic Change, 2020)

Productive behavior in growing kid goats and methane production with the inclusion of chokecherry leaf (Prunus salicifolia) - Lizbeth E. Robles Jimenez; Jose A. Ruiz Perez; Di Lorenzo Nicolas; Alfonso J. Chay Canul; Julio Cesar Ramirez-Rivera; Daniela Villegas-Estrada; Einar Vargas-Bello-Pérez; Manuel Gonzalez-Ronquillo (Tropical Animal Health and Production, 2020)

Ultraflexible lipid vesicles allow topical absorption of cyclosporin A - Juan J Carreras; Willian E Tapia-Ramirez; Adrian Sala; Antonio J Guillot; Teresa M Garrigues; Ana Melero (Drug Delivery and Translational Research, 2020)

Environmental Levels, Sources, and Cancer Risk Assessment of PAHs Associated with PM2.5 and TSP in Monterrey Metropolitan Area - Francisco E. Longoria-Rodríguez; Lucy T. González; Alberto Mendoza; Cesar Leyva-Porras; Alejandro Arizpe-Zapata; Miguel Esneider-Alcalá; Karim Acuña-Askar; Octavio Gaspar-Ramirez; Olivia López-Ayala; Juan M. Alfaro-Barbosa; Oxana V. Kharissova (Archives of Environmental Contamination and Toxicology, 2020)

Numerical simulation of 1-D oil and water displacements in petroleum reservoirs using the correction procedure via reconstruction (CPR) method - G. Galindez-Ramirez; D. K. E. Carvalho; P. R. M. Lyra (Computational Geosciences, 2020)

sFDvent: A global trait database for deep‐sea hydrothermal‐vent fauna - Abbie S. A. Chapman; Stace E. Beaulieu; Ana Colaço; Andrey V. Gebruk; Ana Hilario; Terue C. Kihara; Eva Ramirez‐Llodra; Jozée Sarrazin; Verena Tunnicliffe; Diva J. Amon; Maria C. Baker; Rachel E. Boschen‐Rose; et al. (Global Ecology and Biogeography, 2019)
Motivation Traits are increasingly being used to quantify global biodiversity patterns, with trait databases growing in size and number, across diverse taxa. Despite growing interest in a trait‐based approach to the biodiversity of the deep sea, where the impacts of human activities (including seabed mining) accelerate, there is no single repository for species traits for deep‐sea chemosynthesis‐based ecosystems, including hydrothermal vents. Using an international, collaborative approach, we have compiled the first global‐scale trait database for deep‐sea hydrothermal‐vent fauna – sFDvent ( s Div‐funded trait database for the F unctional D iversity of vent s). We formed a funded working group to select traits appropriate to: (a) capture the performance of vent species and their influence on ecosystem processes, and (b) compare trait‐based diversity in different ecosystems. Forty contributors, representing expertise across most known hydrothermal‐vent systems and taxa, scored species traits using online collaborative tools and shared workspaces. Here, we characterise the sFDvent database, describe our approach, and evaluate its scope. Finally, we compare the sFDvent database to similar databases from shallow‐marine and terrestrial ecosystems to highlight how the sFDvent database can inform cross‐ecosystem comparisons. We also make the sFDvent database publicly available online by assigning a persistent, unique DOI. Main types of variable contained Six hundred and forty‐six vent species names, associated location information (33 regions), and scores for 13 traits (in categories: community structure, generalist/specialist, geographic distribution, habitat use, life history, mobility, species associations, symbiont, and trophic structure). Contributor IDs, certainty scores, and references are also provided. Spatial location and grain Global coverage (grain size: ocean basin), spanning eight ocean basins, including vents on 12 mid‐ocean ridges and 6 back‐arc spreading centres. Time period and grain sFDvent includes information on deep‐sea vent species, and associated taxonomic updates, since they were first discovered in 1977. Time is not recorded. The database will be updated every 5 years. Major taxa and level of measurement Deep‐sea hydrothermal‐vent fauna with species‐level identification present or in progress. Software format .csv and MS Excel (.xlsx).

Soluble Epoxide Hydrolase-Derived Linoleic Acid Oxylipins in Serum Are Associated with Periventricular White Matter Hyperintensities and Vascular Cognitive Impairment - Di Yu; Marie Hennebelle; Demetrios J. Sahlas; Joel Ramirez; Fuqiang Gao; Mario Masellis; Hugo Cogo-Moreira; Richard H. Swartz; Nathan Herrmann; Pak Cheung Chan; Jacqueline A. Pettersen; Donald T. Stuss; et al. (Translational Stroke Research, 2019)

Preparation of Peppermint Oil-Based Nanodevices Loaded with Paclitaxel: Cytotoxic and Apoptosis Studies in HeLa Cells - Sergio E. Flores-Villaseñor; René D. Peralta-Rodríguez; Felipe Padilla-Vaca; H. Iván Meléndez-Ortiz; Jorge C. Ramirez-Contreras; Bernardo Franco (AAPS PharmSciTech, 2019)

Standards and guidelines for canine clinical genetic testing laboratories - Lisa G. Shaffer; Kyle Sundin; Anja Geretschlaeger; Julia Segert; June E. Swinburne; Ramon Royal; Robert Loechel; Christina J. Ramirez; Blake C. Ballif (Human Genetics, 2019)

Whole Genome Sequence Analysis of Burkholderia contaminans FFH2055 Strain Reveals the Presence of Putative β-Lactamases - José J. Degrossi; Cindy Merino; Adela M. Isasmendi; Lorena M. Ibarra; Chelsea Collins; Nicolás E. Bo; Mariana Papalia; Jennifer S. Fernandez; Claudia M. Hernandez; Krisztina M. Papp-Wallace; Robert A. Bonomo; Miryam S. Vazquez; et al. (Current Microbiology, 2019)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

The nitrone spin trap 5,5-dimethyl-1-pyrroline N-oxide dampens lipopolysaccharide-induced transcriptomic changes in macrophages - M. D. Muñoz; M. C. Della Vedova; P. R. Bushel; D. Ganini da Silva; R. P. Mason; Z. Zhai; S. E. Gomez Mejiba; D. C. Ramirez (Inflammation Research, 2018)

First record of the Pacific seahorse Hippocampus ingens in Guadalupe Island, Mexico - E. E. Becerril‐Garcia; D. Petatan‐Ramirez; I. Ortiz‐Aguirre; A. Ayala‐Bocos (Journal of Fish Biology, 2018)
This is the first record of the Pacific seahorse Hippocampus ingens at a northern oceanic island from the eastern Pacific Ocean. The photographic record of the juvenile female H. ingens was made in November 2015 during a cage diving trip at Guadalupe Island, Mexico. The presence of H. ingens in this area could be related to long distance dispersal mechanisms, as has been observed in other species of seahorses.

Fractionation of Dissolved Organic Matter by Co-Precipitation with Iron: Effects of Composition - Yingxun Du; Cesar E. Ramirez; Rudolf Jaffé (Environmental Processes, 2018)

Aerobic interval training reduces vascular resistances during submaximal exercise in obese metabolic syndrome individuals - Ricardo Mora-Rodriguez; V. E. Fernandez-Elias; F. Morales-Palomo; J. G. Pallares; M. Ramirez-Jimenez; J. F. Ortega (European Journal of Applied Physiology, 2017)

User input in iterative design for prevention product development: leveraging interdisciplinary methods to optimize effectiveness - Kate M. Guthrie; Rochelle K. Rosen; Sara E. Vargas; Melissa Guillen; Arielle L. Steger; Melissa L. Getz; Kelley A. Smith; Jaime J. Ramirez; Erna M. Kojic (Drug Delivery and Translational Research, 2017)

Silver-embedded screens in the intensive care unit. A new tool to control multi-drug resistant bacterial cross-transmission - J. Ruiz; P. Ramirez; E. Villarreal; M. Gordon; S. Cuesta; M. Piñol; J. Frasquet; Á. Castellanos (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Response of young bearing olive trees to irrigation-induced salinity - A. Ben-Gal; I. Beiersdorf; U. Yermiyahu; N. Soda; E. Presnov; I. Zipori; R. Ramirez Crisostomo; A. Dag (Irrigation Science, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Unprecedented remote sensing data over King and Rim megafires in the Sierra Nevada Mountains of California - E. Natasha Stavros; Zachary Tane; Van R. Kane; Sander Veraverbeke; Robert J. McGaughey; James A. Lutz; Carlos Ramirez; David Schimel (Ecology, 2016)
Megafires have lasting social, ecological, and economic impacts and are increasing in the western contiguous United States. Because of their infrequent nature, there is a limited sample of megafires to investigate their unique behavior, drivers, and relationship to forest management practices. One approach is to characterize critical information pre‐, during, and post‐fire using remote sensing. In August 2013, the Rim Fire burned 104,131 ha and in September 2014, the King Fire burned 39,545 ha. Both fires occurred in California's Sierra Nevada. The areas burned by these fires were fortuitously surveyed by airborne campaigns, which provided the most recent remote sensing technologies not currently available from satellite. Technologies include an imaging spectrometer spanning the visible to shortwave infrared (0.38–2.5 μm), a multispectral, high‐spatial resolution thermal infrared (3.5–13 μm) spectroradiometer, and Light Detection and Ranging that provide spatial resolutions of pixels from 1 × 1 m to 35 × 35 m. Because of the unique information inherently derived from these technologies before the fires, the areas were subsequently surveyed after the fires. We processed and provide free dissemination of these airborne datasets as products of surface reflectance, spectral metrics and forest structural metrics ( http://dx.doi.org/10.3334/ORNLDAAC/1288 ). These data products provide a unique opportunity to study relationships among and between remote sensing observations and fuel and fire characteristics (e.g., fuel type, condition, structure, and fire severity). The novelty of these data is not only in the unprecedented types of information available from them before, during, and after two megafires, but also in the synergistic use of multiple state of the art technologies for characterizing the environment. The synergy of these data can provide novel information that can improve maps of fuel type, structure, abundance, and condition that may improve predictions of megafire behavior and effects, thus aiding management before, during, and after such events. Key questions that these data could address include: What drives, extinguishes, and results from megafires? How does megafire behavior relate to fire and fuel management? How does the size and severity of a megafire affect the ecological recovery of the system?

Ontogeny changes and weaning effects in gene expression patterns of digestive enzymes and regulatory digestive factors in spotted rose snapper (Lutjanus guttatus) larvae - I. Moguel-Hernández; R. Peña; K. B. Andree; D. Tovar-Ramirez; K. Bonacic; S. Dumas; E. Gisbert (Fish Physiology and Biochemistry, 2016)

Identification of a novel PMS2 alteration c.505C>G (R169G) in trans with a PMS2 pathogenic mutation in a patient with constitutional mismatch repair deficiency - Maureen E. Mork; Ester Borras; Melissa W. Taggart; Amanda Cuddy; Sarah A. Bannon; Y. Nancy You; Patrick M. Lynch; Pedro T. Ramirez; Miguel A. Rodriguez-Bigas; Eduardo Vilar (Familial Cancer, 2016)

Regurgitation Hemodynamics Alone Cause Mitral Valve Remodeling Characteristic of Clinical Disease States In Vitro - Patrick S. Connell; Anam F. Azimuddin; Seulgi E. Kim; Fernando Ramirez; Matthew S. Jackson; Stephen H. Little; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2016)

Comparison of different techniques for the preservation and extraction of phlorotannins in the kelp Lessonia spicata (Phaeophyceae): assays of DPPH, ORAC-PGR, and ORAC-FL as testing methods - E. Cruces; Y. Rojas-Lillo; E. Ramirez-Kushel; E. Atala; C. López-Alarcón; E. Lissi; I. Gómez (Journal of Applied Phycology, 2016)

Cerebral hemovelocity reveals differential resource allocation strategies for extraverts and introverts during vigilance - Tyler H. Shaw; Cynthia Nguyen; Kelly Satterfield; Raul Ramirez; Patrick E. McKnight (Experimental Brain Research, 2016)

Persistence of a single clone of Streptococcus agalactiae causing disease in tilapia ( Oreochromis sp.) cultured in Colombia over 8 years - P Barato; E R Martins; J Melo‐Cristino; C A Iregui; M Ramirez (Journal of Fish Diseases, 2015)

Presence of amphibian chytrid fungus (Batrachochytrium dendrobatidis) in rainwater suggests aerial dispersal is possible - Jonathan E. Kolby; Sara D. Ramirez; Lee Berger; Dale W. Griffin; Merlijn Jocque; Lee F. Skerratt (Aerobiologia, 2015)

Association of KIR3DL1/S1 and HLA-Bw4 with CD4 T cell counts in HIV-infected Mexican mestizos - Daniel Hernández-Ramírez; Mario A. Esparza-Pérez; José L. Ramirez-Garcialuna; J. Rafael Arguello; Peter B. Mandeville; Daniel E. Noyola; Christian A. García-Sepúlveda (Immunogenetics, 2015)

Are there links between responses of soil microbes and ecosystem functioning to elevated CO 2 , N deposition and warming? A global perspective - Pablo García‐Palacios; Martijn L. Vandegehuchte; E. Ashley Shaw; Marie Dam; Keith H. Post; Kelly S. Ramirez; Zachary A. Sylvain; Cecilia Milano de Tomasel; Diana H. Wall (Global Change Biology, 2015)
In recent years, there has been an increase in research to understand how global changes’ impacts on soil biota translate into altered ecosystem functioning. However, results vary between global change effects, soil taxa, and ecosystem processes studied, and a synthesis of relationships is lacking. Therefore, here we initiate such a synthesis to assess whether the effect size of global change drivers (elevated CO 2 , N deposition, and warming) on soil microbial abundance is related with the effect size of these drivers on ecosystem functioning (plant biomass, soil C cycle, and soil N cycle) using meta‐analysis and structural equation modeling. For N deposition and warming, the global change effect size on soil microbes was positively associated with the global change effect size on ecosystem functioning, and these relationships were consistent across taxa and ecosystem processes. However, for elevated CO 2 , such links were more taxon and ecosystem process specific. For example, fungal abundance responses to elevated CO 2 were positively correlated with those of plant biomass but negatively with those of the N cycle. Our results go beyond previous assessments of the sensitivity of soil microbes and ecosystem processes to global change, and demonstrate the existence of general links between the responses of soil microbial abundance and ecosystem functioning. Further we identify critical areas for future research, specifically altered precipitation, soil fauna, soil community composition, and litter decomposition, that are need to better quantify the ecosystem consequences of global change impacts on soil biodiversity.

Safety and Biocompatibility of Carbohydrate-Functionalized Polyanhydride Nanoparticles - Julia E. Vela-Ramirez; Jonathan T. Goodman; Paola M. Boggiatto; Rajarshi Roychoudhury; Nicola L. B. Pohl; Jesse M. Hostetter; Michael J. Wannemuehler; Balaji Narasimhan (The AAPS Journal, 2015)

Improving Environmental and Social Targeting through Adaptive Management in Mexico's Payments for Hydrological Services Program - KATHARINE R. E. SIMS; JENNIFER M. ALIX‐GARCIA; ELIZABETH SHAPIRO‐GARZA; LEAH R. FINE; VOLKER C. RADELOFF; GLEN ARONSON; SELENE CASTILLO; CARLOS RAMIREZ‐REYES; PATRICIA YAÑEZ‐PAGANS (Conservation Biology, 2014)
Natural resource managers are often expected to achieve both environmental protection and economic development even when there are fundamental trade‐offs between these goals. Adaptive management provides a theoretical structure for program administrators to balance social priorities in the presence of trade‐offs and to improve conservation targeting. We used the case of Mexico's federal Payments for Hydrological Services program (PSAH) to illustrate the importance of adaptive management for improving program targeting. We documented adaptive elements of PSAH and corresponding changes in program eligibility and selection criteria. To evaluate whether these changes resulted in enrollment of lands of high environmental and social priority, we compared the environmental and social characteristics of the areas enrolled in the program with the characteristics of all forested areas in Mexico, all areas eligible for the program, and all areas submitted for application to the program. The program successfully enrolled areas of both high ecological and social priority, and over time, adaptive changes in the program's criteria for eligibility and selection led to increased enrollment of land scoring high on both dimensions. Three factors facilitated adaptive management in Mexico and are likely to be generally important for conservation managers: a supportive political environment, including financial backing and encouragement to experiment from the federal government; availability of relatively good social and environmental data; and active participation in the review process by stakeholders and outside evaluators. Mejorando los Objetivos Ambiental y Social Mediante el Manejo Adaptativo en el Programa de Pagos por Servicios Hidrológicos en México

Climate‐driven spatial mismatches between British orchards and their pollinators: increased risks of pollination deficits - Chiara Polce; Michael P Garratt; Mette Termansen; Julian Ramirez‐Villegas; Andrew J Challinor; Martin G Lappage; Nigel D Boatman; Andrew Crowe; Ayenew Melese Endalew; Simon G Potts; Kate E Somerwill; Jacobus C Biesmeijer (Global Change Biology, 2014)
Understanding how climate change can affect crop‐pollinator systems helps predict potential geographical mismatches between a crop and its pollinators, and therefore identify areas vulnerable to loss of pollination services. We examined the distribution of orchard species (apples, pears, plums and other top fruits) and their pollinators in Great Britain, for present and future climatic conditions projected for 2050 under the SRES A1B Emissions Scenario. We used a relative index of pollinator availability as a proxy for pollination service. At present, there is a large spatial overlap between orchards and their pollinators, but predictions for 2050 revealed that the most suitable areas for orchards corresponded to low pollinator availability. However, we found that pollinator availability may persist in areas currently used for fruit production, which are predicted to provide suboptimal environmental suitability for orchard species in the future. Our results may be used to identify mitigation options to safeguard orchard production against the risk of pollination failure in Great Britain over the next 50 years; for instance, choosing fruit tree varieties that are adapted to future climatic conditions, or boosting wild pollinators through improving landscape resources. Our approach can be readily applied to other regions and crop systems, and expanded to include different climatic scenarios.

Synthesis, characterization, and evaluation of cis-diphenyl pyridineamine platinum(II) complexes as potential anti-breast cancer agents - Jacqueline Gamboa Varela; Atasi De Chatterjee; Priscilla Guevara; Verenice Ramirez; Alejandro J. Metta-Magaña; Dino Villagrán; Armando Varela-Ramirez; Siddhartha Das; Jose E. Nuñez (JBIC Journal of Biological Inorganic Chemistry, 2014)

Dimorphism and hydrocarbon metabolism in Yarrowia lipolytica var. indica - A. S. Palande; S. V. Kulkarni; C. León-Ramirez; E. Campos-Góngora; J. Ruiz-Herrera; M. V. Deshpande (Archives of Microbiology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

A phytosociological survey of some serpentine plant communities in the Dominican Republic - E. Cano; A. Cano-Ortiz; S. Del Río; A. Veloz Ramirez; F. J. Esteban Ruiz (Plant Biosystems, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Antioxidant enzymes gene expression and antihypertensive effects of seaweeds Ulva linza and Lessonia trabeculata in rats fed a high-fat and high-sucrose diet - Abril Ramirez-Higuera; Lucía Quevedo-Corona; Norma Paniagua-Castro; Germán Chamorro-Ceballos; Angel Milliar-Garcia; María E. Jaramillo-Flores (Journal of Applied Phycology, 2014)

Xenobiotic metabolizing enzyme activities in cells used for testing skin sensitization in vitro - E. Fabian; D. Vogel; V. Blatz; T. Ramirez; S. Kolle; T. Eltze; B. van Ravenzwaay; F. Oesch; R. Landsiedel (Archives of Toxicology, 2013)

Predictors of regional establishment success and spread of introduced non‐indigenous vertebrates - Craig R. Allen; Kristine T. Nemec; Donald A. Wardwell; Justin D. Hoffman; Mathew Brust; Karie L. Decker; Daniel Fogell; Jennifer Hogue; Aaron Lotz; Thaddeus Miller; Marcy Pummill; Luis E. Ramirez‐Yañez; et al. (Global Ecology and Biogeography, 2013)
Aim To provide the first analysis of predictors of both establishment and spread, both within and across taxa, for all vertebrate taxa within a region. We used F lorida, USA , as our study system because it has a well‐documented history of introduction and invasion, and is a hotspot for biological invasions. Location F lorida, USA. Methods We analysed non‐indigenous species ( NIS ) data from peninsular F lorida – which included both successful and unsuccessful introductions from all vertebrate classes – to determine the best predictors of both establishment and spread for fish (65 species), herpetofauna (63 species), birds (71 species) and mammals (25 species). We used 10 variables proposed to be associated with the establishment and spread of NIS : body mass, geographic origin, reproductive rate, diet generalism, native‐range size, latitude of native range, number of NIS present at date of introduction, presence of NIS congeners, morphological proximity to other NIS (in terms of body mass) and propagule pressure. A multimodel selection process was used with an information‐theoretic approach to determine the best fit models for predicting establishment and spread of NIS . We selected a priori plausible predictive models for establishment and spread. Results Large native‐range size and small body mass best predicted establishment of non‐indigenous herpetofauna. The presence of NIS congeners had the largest positive effect on the establishment of non‐indigenous fish. For mammals, the number of NIS present at the time of introduction best explained establishment. No single model best explained bird establishment. For all taxa but birds, the number of NIS present at time of introduction was included in at least one of the best‐supported models for explaining spread. Main conclusions Our analyses suggest that predictors of establishment and spread differ across vertebrate taxa at the scale studied. Most predictive variables can be interpreted as measures of competitive interactions among species.

Novel Mutations Mapping to the Fourth Sodium Channel Domain of Nav1.7 Result in Variable Clinical Manifestations of Primary Erythromelalgia - Roman Cregg; Bisola Laguda; Robert Werdehausen; James J. Cox; John E. Linley; Juan D. Ramirez; Istvan Bodi; Michael Markiewicz; Kevin J. Howell; Ya-Chun Chen; Karen Agnew; Henry Houlden; et al. (NeuroMolecular Medicine, 2013)

Steep clines within a highly permeable genome across a hybrid zone between two subspecies of the E uropean rabbit - Miguel Carneiro; Stuart J. E. Baird; Sandra Afonso; Esther Ramirez; Pedro Tarroso; Henrique Teotónio; Rafael Villafuerte; Michael W. Nachman; Nuno Ferrand (Molecular Ecology, 2013)
Maintenance of genetic distinction in the face of gene flow is an important aspect of the speciation process. Here, we provide a detailed spatial and genetic characterization of a hybrid zone between two subspecies of the European rabbit. We examined patterns of allele frequency change for 22 markers located on the autosomes, X ‐chromosome, Y ‐chromosome and mt DNA in 1078 individuals sampled across the hybrid zone. While some loci revealed extremely wide clines ( w ≥ 300 km) relative to an estimated dispersal of 1.95–4.22 km/generation, others showed abrupt transitions ( w ≈ 10 km), indicating localized genomic regions of strong selection against introgression. The subset of loci showing steep clines had largely coincident centers and stepped changes in allele frequency that did not co‐localize with any physical barrier or ecotone, suggesting that the rabbit hybrid zone is a tension zone. The steepest clines were for X ‐ and Y ‐chromosome markers. Our results are consistent with previous inference based on DNA sequence variation of individuals sampled in allopatry in suggesting that a large proportion of each genome has escaped the overall barrier to gene flow in the middle of the hybrid zone. These results imply an old history of hybridization and high effective gene flow and anticipate that isolation factors should often localize to small genomic regions.

Influence of human immune cells on cancer: studies at the University of Colorado - Tullia C. Bruno; Jena D. French; Kimberly R. Jordan; Oscar Ramirez; Trisha R. Sippel; Virginia F. Borges; Bryan R. Haugen; Martin D. McCarter; Allen Waziri; Jill E. Slansky (Immunologic Research, 2013)

A Short-Term Scan–Rescan Reliability Test Measuring Brain Tissue and Subcortical Hyperintensity Volumetrics Obtained Using the Lesion Explorer Structural MRI Processing Pipeline - Joel Ramirez; Christopher J. M. Scott; Sandra E. Black (Brain Topography, 2013)

Friedreich's Ataxia Causes Redistribution of Iron, Copper, and Zinc in the Dentate Nucleus - Arnulf H. Koeppen; R. Liane Ramirez; Devin Yu; Sarah E. Collins; Jiang Qian; Patrick J. Parsons; Karl X. Yang; Zewu Chen; Joseph E. Mazurkiewicz; Paul J. Feustel (The Cerebellum, 2012)

A way forward on adaptation to climate change in Colombian agriculture: perspectives towards 2050 - Julian Ramirez-Villegas; Mike Salazar; Andy Jarvis; Carlos E. Navarro-Racines (Climatic Change, 2012)

Soil properties following reforestation or afforestation of marginal cropland - Thomas J. Sauer; David E. James; Cynthia A. Cambardella; Guillermo Hernandez-Ramirez (Plant and Soil, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Population structure and reproductive patterns of the NW Mediterranean deep-sea macrourid Trachyrincus scabrus (Rafinesque, 1810) - U. Fernandez-Arcaya; L. Recasens; H. Murua; E. Ramirez-Llodra; G. Rotllant; J. B. Company (Marine Biology, 2012)

Vertical density gradient in the eastern North Atlantic during the last 30,000 years - M. Rogerson; G. R. Bigg; E. J. Rohling; J. Ramirez (Climate Dynamics, 2012)

Effects of temperature during soybean seed development on defense-related gene expression and fungal pathogen accumulation - Robert G. Upchurch; Martha E. Ramirez (Biotechnology Letters, 2011)

Optimization of gene delivery methods in Xenopus laevis kidney (A6) and Chinese hamster ovary (CHO) cell lines for heterologous expression of Xenopus inner ear genes - Daniel Ramirez-Gordillo; Casilda Trujillo-Provencio; V. Bleu Knight; Elba E. Serrano (In Vitro Cellular & Developmental Biology - Animal, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

A comparative analysis of microflora during biofilm development on grape seeds exposed to methanol in a biofilter - R. Moreno-Terrazas; F. J. Flores-Tena; M. D. Barba-Avila; A. L. Guerrero-Barrera; F. J. Avelar-Gonzalez; E. M. Ramirez-Lopez (World Journal of Microbiology and Biotechnology, 2010)

Scared sick? Predator–pathogen facilitation enhances exploitation of a shared resource - Ricardo A. Ramirez; William E. Snyder (Ecology, 2009)
Resource use generally increases with greater consumer diversity, an effect often attributed to resource partitioning. Pathogens and predators are two classes of consumer that exhibit differences in ecologically important traits (e.g., size, resource acquisition strategy, foraging location) that could lead to complementary effects on shared prey/hosts. To examine this possibility, we manipulated diversity among a community of predators and pathogens that together attack an herbivorous beetle, Leptinotarsa decemlineata , and measured resulting effects on herbivore suppression and resulting plant damage. We found that herbivore mortality increased, and plant damage decreased, when more natural enemy species were present. However, closer examination revealed that it was the pairing of predator with pathogen species, rather than greater biodiversity per se, that strengthened herbivore suppression. In this community, predators occur aboveground, attacking herbivore juvenile stages feeding on plant foliage, whereas pathogens occur belowground and attack herbivores pupating in the soil. In a subsequent field experiment, we tracked the emergence of predator–pathogen complementarity throughout the course of beetle development. We found that herbivores exposed to predators aboveground were more susceptible to subsequent pathogen infection belowground, consistent with our observation in the laboratory that predator exposure weakens beetles' immune response. Thus, predators facilitated resource capture by pathogens, perhaps reflecting an inherent conflict for the herbivore in allocating energetic resources toward anti‐predator vs. anti‐pathogen defenses. Our results suggest that predator–pathogen combinations were particularly taxing not because the consumer species partitioned resources among themselves, but instead because they enforced the partitioning of resources internal to prey/host individuals.

Hydrogen sulfide removal from air by Acidithiobacillus thiooxidans in a trickle bed reactor - M. Ramirez; J. M. Gómez; D. Cantero; J. Páca; M. Halecký; E. I. Kozliak; M. Sobotka (Folia Microbiologica, 2009)

Short term changes in dynamics of C and N in soil when crops are cultivated on permanent raised beds - E. Verachtert; B. Govaerts; K. Lichter; K. D. Sayre; J. M. Ceballos-Ramirez; M. L. Luna-Guido; J. Deckers; L. Dendooven (Plant and Soil, 2009)

Monocyte Chemotactic Protein-1 Regulates Voltage-Gated K+ Channels and Macrophage Transmigration - Howard E. Gendelman; Shengyuan Ding; Nan Gong; Jianuo Liu; Servio H. Ramirez; Yuri Persidsky; R. Lee Mosley; Tong Wang; David J. Volsky; Huangui Xiong (Journal of Neuroimmune Pharmacology, 2009)

Widespread expression of inducible NOS and citrulline in lupus nephritis tissues - J. J. Bollain-y-Goytia; R. Ramírez-Sandoval; L. Daza; E. Esparza; O. Barbosa; D. Ramirez; G. Pacheco-Tovar; E. Avalos-Diaz; C. Rodríguez-Padilla; R. Herrera-Esparza (Inflammation Research, 2009)

Hypercalcemia due to an interaction of all-trans retinoic acid (ATRA) and itraconazole therapy for acute promyelocytic leukemia successfully treated with zoledronic acid - R. Cordoba; E. Ramirez; S. H. Lei; A. Lopez de la Guia; M. J. Sanjurjo; A. J. Carcas; F. Hernandez-Navarro (European Journal of Clinical Pharmacology, 2008)

The importance of sample size, log-mean ratios, and intrasubject variability in the acceptance criteria of 108 bioequivalence studies - E. Ramirez; P. Guerra; O. Laosa; B. Duque; B. Tabares; S. H. Lei; A. J. Carcas; J. Frias (European Journal of Clinical Pharmacology, 2008)

Probability distributions for carbon emissions and atmospheric response - Clifford E. Singer; T. S. Gopi Rethinaraj; Samuel Addy; David Durham; Murat Isik; Madhu Khanna; Brandon Kuehl; Jianding Luo; Wilma Quimio; Kothavari Rajendran; Donna Ramirez; Ji Qiang; et al. (Climatic Change, 2008)

Proteinuria, GGT Index and Fractional Clearance of Electrolytes in Exercising Athletic Horses - P. Scarpa; V. Di Fabio; C. Ramirez; L. Baggiani; E. Ferro (Veterinary Research Communications, 2007)

Comparative phylogeography of Trypanosoma rangeli and Rhodnius (Hemiptera: Reduviidae) supports a long coexistence of parasite lineages and their sympatric vectors - F. MAIA DA SILVA; A. C. V. JUNQUEIRA; M. CAMPANER; A. C. RODRIGUES; G. CRISANTE; L. E. RAMIREZ; Z. C. E. CABALLERO; F. A. MONTEIRO; J. R. COURA; N. AÑEZ; M. M. G. TEIXEIRA (Molecular Ecology, 2007)
To make reliable interpretations about evolutionary relationships between Trypanosoma rangeli lineages and their insect vectors (triatomine bugs of the genus Rhodnius ) and, thus, about the determinant factors of lineage segregation within T. rangeli , we compared phylogenies of parasite isolates and vector species. Sixty‐one T. rangeli isolates from invertebrate and vertebrate hosts were initially evaluated in terms of polymorphism of the spliced‐leader gene (SL). Further analysis based on SL and SSUrRNA sequences from 33 selected isolates, representative of the overall phylogenetic diversity and geographical range of T. rangeli , supported four phylogenetic lineages within this species. By comparing the phylogeny of Rhodnius species with that inferred for T. rangeli isolates and through analysis of the geographical range of the isolates, we showed that there is a very significant overlap in the distribution of Rhodnius species and T. rangeli lineages. Congruence between phylogeographical analysis of both T. rangeli lineages and complexes of Rhodnius species are consistent with the hypothesis of a long coexistence of parasites and their vectors, with lineage divergence associated with sympatric species of Rhodnius apparently without association with particular vertebrate hosts. Separation of T. rangeli isolates from vectors of distinct complexes living in sympatry favours the absence of gene flow between the lineages and suggests evolution of T. rangeli lineages in independent transmission cycles, probably associated to specific Rhodnius spp. ecotopes. A polymerase chain reaction assay based on SL intergenic sequences was developed for simultaneous identification and lineage genotyping of T. rangeli in epidemiological surveys.

Multisensory processing and oscillatory activity: analyzing non-linear electrophysiological measures in humans and simians - Daniel Senkowski; Manuel Gomez-Ramirez; Peter Lakatos; Glenn R. Wylie; Sophie Molholm; Charles E. Schroeder; John J. Foxe (Experimental Brain Research, 2007)

The physical–chemical habitat of the Buenos Aires pejerrey, Odontesthes bonariensis (Teleostei, Atherinopsidae), with a proposal of a water quality index - Sergio E. Gómez; Roberto C. Menni; Jimena Gonzalez Naya; Luciana Ramirez (Environmental Biology of Fishes, 2007)

Presence of HTLV-I Tax protein in cerebrospinal fluid from HAM/TSP patients - L. Cartier; E. Ramirez (Archives of Virology, 2005)

Long-term changes in reproductive patterns of the holothurian Oneirophanta mutabilis from the Porcupine Abyssal Plain - E. Ramirez-Llodra; W. D. K. Reid; D. S. M. Billett (Marine Biology, 2005)

In vitro cytoskeleton changes of mouse neurons induced by purified HTLV-1, and PBMC from HAM/TSP patients and HTLV-1 carriers - E. Ramirez; L. Cartier; R. Flores (Archives of Virology, 2004)

Reproductive strategies of two deep-sea gastropod species from the Porcupine Seabight (Northeast Atlantic) - C. Olabarria; E. Ramirez-Llodra (Marine Biology, 2004)

Bovine Red Blood Cell Ghost Cholinesterase as a Monitoring Standard - A. Ramirez; E. DePeters; D. Bosworth; B. W. Wilson; D. Arrieta (Bulletin of Environmental Contamination and Toxicology, 2003)

Glaciers and Climate in the Andes between the Equator and 30° S: What is Recorded under Extreme Environmental Conditions? - U. Schotterer; M. Grosjean; W. Stichler; P. Ginot; C. Kull; H. Bonnaveira; B. Francou; H. W. Gäggeler; R. Gallaire; G. Hoffmann; B. Pouyaud; E. Ramirez; et al. (Climatic Change, 2003)

Acmella radicans var. radicans: In vitro culture establishment and alkamide content - P. Rios-Chavez; E. Ramirez-Chavez; C. Armenta-Salinas; J. Molina-Torres (In Vitro Cellular & Developmental Biology - Plant, 2003)

Reproductive biology of porcellanasterid asteroids from three abyssal sites in the northeast Atlantic with contrasting food input - Ramirez-Llodra E.; Tyler P.; Billett D. (Marine Biology, 2002)

Gametogenesis, spawning behavior, and early development in the "iceworm" Hesiocaeca methanicola (Polychaeta: Hesionidae) from methane hydrates in the Gulf of Mexico - K. J. Eckelbarger; C. M. Young; E. Ramirez Llodra; S. Brooke; P. Tyler (Marine Biology, 2001)

Deep molecular divergence in the absence of morphological and ecological change in the Californian coastal dune endemic trapdoor spider Aptostichus simus - J. E. Bond; M. C. Hedin; M. G. Ramirez; B. D. Opell (Molecular Ecology, 2001)
Aptostichus simus is a trapdoor spider endemic to the coastal dunes of central and southern California and, on morphological grounds, is recognized as a single species. Mitochondrial DNA 16S rRNA sequences demonstrate that most populations are fixed for the same haplotype and that the population haplotypes from San Diego County, Los Angeles County, Santa Rosa Island, and Monterey County are extremely divergent (6–12%), with estimated separation times ranging from 2 to 6 million years. A statistical cluster analysis of morphological features demonstrates that this genetic divergence is not reflected in anatomical features that might signify ecological differentiation among these lineages. The species status of these divergent populations of A. simus depends upon the species concept utilized. If a time‐limited genealogical perspective is employed, A. simus would be separated at the base into two genetically distinct species. This study suggests that species concepts based on morphological distinctiveness, in spider groups with limited dispersal capabilities, probably underestimate true evolutionary diversity.

Different effects of corticosteroid-induced muscle wasting compared with undernutrition on rat diaphragm energy metabolism - Esther Koerts-de Lang; Annemie M. W. J. Schols; Olav E. Rooyackers; Ghislaine Gayan-Ramirez; Emiel F. M. Wouters; Marc Decramer (European Journal of Applied Physiology, 2000)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Rapid test for determination of urea hydrolysis - S. M. Hussain Qadri; Sabiha Zubairi; H. P. Hawley; H. H. Mazlaghani; E. G. Ramirez (Antonie van Leeuwenhoek, 1984)